REGISTERS OF DEBATES USED BY MALANG DEBATING UNION - WAHYUNINGTIYAS, NONY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: Sociolinguistics, Register, English debate, Malang Debating Union, Debater. English debate becomes one of popular competitions which is participated by senior high school and university students. This activity aims to improve English speaking skill and sharpen critical thinking. One of communities which gets involved in English debate is Malang Debating Union (MDU). As a community, MDU has registers which are used to interact with each other during practice time. Hence, in this research, the writer formulates two problems to discuss: (1) What the registers are used by debaters in MDU and (2) How are the situational contexts dealing with participants, relation among participants, and communicative purpose performed by debaters in MDU. In answering those problems, the writer applies theory of register proposed by Biber and Conrad (2009) which focuses on situational context.This research belongs to qualitative research which uses utterances containing registers delivered by debaters and adjudicator (juror) during practice times as the data. The writer undergoes observation, recording, transcribing, highlighting, and interview to collect the data. Meanwhile, the writer goes for classifying registers within a table, describing register application in relation to situational contexts, applying data triangulation from field notes and result of interview on checking the data and drawing conclusion.In this research, the writer finds 14 registers which have similar meaning with the literal one, but they are different in use. In terms of situational contexts, there are 3 participants involved in the debate: adjudicator (juror), government/positive and opposition/negative team. Adjudicator has higher power in deciding the winner of the debate compared to the two teams. Therefore, the communicative purposes applied by him are informing, announcing, and providing procedural information about how to perform certain activities or suggesting what needs to add within argumentation. Meanwhile, government team and opposition team occupy themselves as rivals during the debate. As the result, the communicative purposes come up to argue or break down the opponent’s argument and persuade the adjudicator (juror) to go with their team’s argument.Based on the result of this research, the writer suggests that the next researchers who are interested in conducting the same topic take other communities, such as mass media community. In addition, the next researchers might analyze the same object related to debate community by using different linguistics branches, such as Pragmatics (speech act) or Second Language Acquisition (error in grammar or pronunciation).